Exosomal circCOL1A1 promotes angiogenesis via recruiting EIF4A3 protein and activating Smad2/3 pathway in colorectal cancer - Gui Hu; Changwei Lin; Kai Gao; Miao Chen; Fei Long; Buning Tian (BMC, 2023)
Abstract Background Colorectal cancer (CRC) is the third frequently diagnosed cancer with high incidence and mortality rate worldwide. Our previous report has demonstrated that circCOL1A1 (hsa_circ_0044556) functions as an oncogene in CRC, and Gene Ontology (GO) analysis has also revealed the strong association between circCOL1A1 and angiogenesis. However, the mechanism of circCOL1A1 or exosomal circCOL1A1 in CRC angiogenesis remains elusive. Methods Purified exosomes from CRC cells were characterized by nanoparticle tracking analyzing, electron microscopy and western blot. qRT-PCR, immunohistochemistry or western blot were employed to test the expression of circCOL1A1, EIF4A3, Smad pathway and angiogenic markers. Cell proliferation of HUVECs was monitored by CCK-8 assay. The migratory and angiogenic capabilities of HUVECs were detected by wound healing and tube formation assay, respectively. Bioinformatics analysis, RNA immunoprecipitation (RIP), RNA pull-down and FISH assays were used to detect the interactions among circCOL1A1, EIF4A3 and Smad2/3 mRNA. The in vitro findings were verified in xenograft model. Results CRC cell-derived exosomal circCOL1A1 promoted angiogenesis of HUVECs via recruiting EIF4A3. EIF4A3 was elevated in CRC tissues, and it stimulated angiogenesis of HUVECs through directly binding and stabilizing Smad2/3 mRNA. Moreover, exosomal circCOL1A1 promoted angiogenesis via inducing Smad2/3 signaling pathway in vitro, and it also accelerated tumor growth and angiogenesis in vivo. Conclusion CRC cell-derived exosomal circCOL1A1 promoted angiogenesis via recruiting EIF4A3 and activating Smad2/3 signaling.